Efficiency of 76-GHz post-wall waveguide-fed parallel-plate slot arrays. - Hirokawa, J. (IEEE Transactions on antennas and propagation)
We design and fabricate various sizes of 76-GHz post-wall waveguide-fed parallel-plate slot arrays. The post-wall waveguide is an array of metalized via-holes with a narrow spacing in a grounded dielectric substrate. The antenna can be easily made at low cost by conventional PCB (printed circuit board) fabrication techniques such as via-holing, metal plating, and etching. We have obtained 40-50% efficiency for various sizes from 26 mm×24 mm to 104 mm×100 mm. We have measured 35.3 dBi gain with 39.3% efficiency at 77.0 GHz in an antenna sized 104 mm×100 mm